2018
DOI: 10.1016/j.chemgeo.2018.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-182 in the upper continental crust: Evidence from glacial diamictites

Abstract: Study of igneous and sedimentary rocks that may be representative of the chemical and isotopic characteristics of portions of the upper continental crust (UCC) has provided important insights to the origin and growth of the continents, as well as the large-scale chemical evolution of the silicate Earth. For example, changes in the major and trace element compositions, as well as long-lived radiogenic isotope systematics of (meta)sedimentary rocks through time have led to the conclusion that at least some porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 49 publications
2
28
2
Order By: Relevance
“…However, the reason these effects are either absent or too small to be observed for the metal fractions measured by TIMS is unclear. Differences in bulk composition (i.e., metal vs. silicate-oxide matrices) of the samples are unlikely to be the cause, as previously reported 183 W values for terrestrial, silicate-oxide dominated samples also measured by TIMS appear to be free from these effects (e.g., Mundl et al, 2018). We speculate that it could be due to different column dimensions for the two procedures, or different abundances of W in metals vs. nonmagnetic and slightly magnetic fractions, or the formation of hydrides within the plasma, as proposed by Breton and Quitté (2014).…”
Section: Hafnium and W Abundances 182 Hf-182 W Isotopic Compositionsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the reason these effects are either absent or too small to be observed for the metal fractions measured by TIMS is unclear. Differences in bulk composition (i.e., metal vs. silicate-oxide matrices) of the samples are unlikely to be the cause, as previously reported 183 W values for terrestrial, silicate-oxide dominated samples also measured by TIMS appear to be free from these effects (e.g., Mundl et al, 2018). We speculate that it could be due to different column dimensions for the two procedures, or different abundances of W in metals vs. nonmagnetic and slightly magnetic fractions, or the formation of hydrides within the plasma, as proposed by Breton and Quitté (2014).…”
Section: Hafnium and W Abundances 182 Hf-182 W Isotopic Compositionsmentioning
confidence: 85%
“…Archer et al (2017) compared the results of samples measured using the two procedures detailed above, and reported that the 182 W and 183 W isotopic compositions were identical within uncertainties. Mundl et al (2018) also compared data for NIST steel standard 129c processed using these two procedures, and found that the 182 W and 183 W isotopic compositions were also in agreement within uncertainties.…”
Section: Separation and Purification Of W For Isotopic Compositions-mmentioning
confidence: 96%
“…Transparent green diamonds are samples where ages have not been reliably determined using U‐Pb zircon methods. Note that all negative μ 182 W values from the Archean, including diamictite analyses, come from South Africa and may be a locally derived signal (Mundl et al, 2018). Inset shows the same plot with only felsic rocks and diamictites.…”
Section: Discussionmentioning
confidence: 99%
“…Mundl et al . ), requires a Ti/W < 1. The use of oxidising organic acid solutions on anion exchange resins has previously been employed to chemically separate Ti from W (Kleine et al .…”
mentioning
confidence: 99%